Α, BK-Contractions in Bipolar Metric Spaces. (26th February 2021) - Gaba, Yaé Ulrich; Aphane, Maggie; Aydi, Hassen
Abstract : In this paper, we introduce the concept of α, BK -contractions and prove the existence of fixed points for contravariant mappings on bipolar metric spaces.